What the Pokemon Go have study adolescents for? - Khlomov K.D; Davydov D.G (Moscow State University of Psychology and Education, 2018)
The paper reports the results of the research on the adolescents - Pokemon Go players. The hypotheses towards the role of the games with virtual and augmented reality within the modern society presented in the scientific literature are discussed. The aim of this research was to check the link between personal characteristics, the social situation factors (e.g. family context), young men images about him or herself, and meaning and personal value of the game. The results of the structured interviews with 44 adolescents playing Pokemon Go on the street are given; the players' representations towards themselves, their social environment, and the game are discovered. The conclusions about the meaning of the virtual, geographic, and social realities integration and social and family environment influence on the game involvement are made. The psychological mechanisms of the involvement into the game and the role of the social and family environment are discussed. In this article was made the conclusions about the role of virtual, geographic, social reality integration, social and family role, and psychological mechanism to be involved in the game. Subjective space transformation and the changes in everyday city landscape meanings conditioned by the game are discussed. The game allows the adolescents and youth to see the reality out of the everyday routine.